Effect of Liandouqingmai recipe on quality of life and inflammatory reactions of patients with coronary heart disease - Zhu, Hongjun; Lu, Shu; Su, Wei; Gong, Shaoyu; Zhang, Zhibin; Li, Ping (Journal of traditional Chinese medicine, 2014)
OBJECTIVE： To observe the effect of Liandouqingmai recipe（Chinese herbal medicine compound preparation） on the quality of life（QOL） and inflammatory reaction of patients with coronary heart disease（CHD）.METHODS： A total of 101 CHD patients were randomized into two groups： treatment group（n=45）receiving standard treatment for CHD plus Liandouqingmai recipe, and control group（n=56） receiving standard treatment only. The control group contained 16 normal healthy subjects. Changes in hs-C-reactive protein（CRP）, peripheral blood leucocytes（PBL）, and interleukin（IL）-6 and IL-10 levels were measured. The Seattle Angina Questionnaire（SAQ） was used to determine patient QOL before and after treatment for 2 weeks.RESULTS： Before treatment, SAQ scores [physical limitation（PL）, angina stability（AS）, angina frequen-cy（AF）, treatment satisfaction（TS）, and disease perception（DP）] were not statistically different between groups. After treatment, AS and DP levels of controls were significantly increased compared with the other groups, while PL, AS, AF, TS, and DP levels of the treatment group were significantly increased compared with controls. Treatment group SAQ scores（PL, AS, AF, TS, and DP） were significantly higher than for controls. CHD patient IL-6 and IL-10 levels were significantly higher than controls.Before treatment, mean levels of IL-6, hs-CRP and PBL of the two groups were not statistically different. After treatment, mean levels of IL-6, IL-10,hs-CRP and PBL of the two groups were significantly decreased compared with their before treatment values, and levels of IL-6, hs-CRP, and PBL of the treatment group were lower than controls. Although mean IL-10 levels of both groups decreased, there was no significant difference in between-group and in-group comparisons before and after treatment. Mean levels of IL-6 and IL-10 in the normal group were lower than in CHD patients.SAQ scores of QOL were negatively associated with the inflammatory index（IL-6/IL-10）, and there was a significant negative association of IL-10 with AS（r=﹣0.15, P〈0.05）.CONCLUSION： Inflammatory reactions in CHD patients are related to angina status. Coadministration of CHD standard treatment and Liandouqingmai recipe increased patient SAQ scores by decreasing IL-6, IL-10, hs-CRP, and PBL levels in CHD patients, which might inhibit endothelial inflammation to improve patient QOL.